Intertwining Operators between Two Orthogonal Projections. (25th October 2020) - Deng, Chunyuan; Liang, Wenting
Abstract: Let P and Q be a pair of orthogonal projections. In this note we will prove that there exists a unitary U ∈ B ( H ) such that UP = QU and UQ = PU if and only if dim [ R ( P ) ∩ N ( Q ) ] = dim [ N ( P ) ∩ R ( Q ) ] .